2015
DOI: 10.1016/j.ahj.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of new-onset atrial fibrillation after coronary artery bypass grafting surgery

Abstract: BACKGROUND Postoperative atrial fibrillation (AF) is a potentially life-threatening complication after coronary artery bypass graft (CABG) surgery. Genetic predisposition may predict risk for developing postoperative AF. METHODS Study subjects underwent CABG surgery with cardiopulmonary bypass at Duke University Medical Center. In a discovery cohort of 877 individuals from the Perioperative Genetics and Safety Outcomes Study (PEGASUS), we performed a genome-wide association study (GWAS) using a logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
0
20
1
Order By: Relevance
“…This database was collected with a target sample size of n = 1004 patients undergoing various cardiac surgical procedures and has been detailed in previous manuscripts. 17 A STROBE diagram detailing cohort selection is shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…This database was collected with a target sample size of n = 1004 patients undergoing various cardiac surgical procedures and has been detailed in previous manuscripts. 17 A STROBE diagram detailing cohort selection is shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…Kertai et al conducted a gene-wide association study in two cohorts of patients (diversity, n = 877 and validation, n = 304) to investigate the link of a genetic polymorphism in lymphocyte antigen 96 (LY96) with POAF incidence in CABG patients [43]. Based on SNPs selection criteria, they recognized only the minor allele of rs10504554, in the intronic region of the LY96, which exhibited a lower risk for POAF in both data sets (discovery data set: OR 0.48, 95% CI 0.34-0.68, p < 0.01, and replication dataset: OR 0.55, 95% CI 0.31-0.99, p = 0.046).…”
Section: Single Nucleotide Polymorphisms (Snps)mentioning
confidence: 99%
“…We also noted that most of the studies have shown only discovery group and the results were not validated in the independent validation group. Only two studies showed results for both the discovery and the validation groups [48], [43]. Most of the studies have patient population w/wo preexisting AF.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subsequent likely candidate gene(s) can then be studied in a confirmatory patient population. 32,60,61 Genetic information gained can be used in a preemptive fashion, with genome identification using polymorphisms that are known and available at the time of prescribing and accompanying clinical decision support incorporated into the electronic health record. 57 Investigators who prospectively performed genetic testing on patients scheduled for coronary arteriography recently reported using this method.…”
Section: Applicationmentioning
confidence: 99%